IET Intelligent Signal Processing Conference 2013 (ISP 2013) 2013
DOI: 10.1049/cp.2013.2066
|View full text |Cite
|
Sign up to set email alerts
|

Angle of Arrival Estimation for Broadband Signals: A Comparison

Abstract: This paper reviews and compares three different linear algebraic signal subspace techniques for angle of arrival estimation. These include a polynomial matrix approach to multiple signal classification (MUSIC), a parameterised spatial covariance matrix approach, and an auto-focussing based version of coherent signal subspace estimation applied to MUSIC. These approaches are expressed in the framework of polynomial space-time covariance matrices and their polynomial eigenvalue decomposition, thus highlighting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 10 publications
(21 reference statements)
0
11
0
Order By: Relevance
“…where R x k x k (τ ) is the space-time covariance matrix obtained following (5) in the k th frame of length L, such that n ∈ {(k − 1)L, . .…”
Section: Batch Mode Versus Frame-based Enhancementmentioning
confidence: 99%
See 1 more Smart Citation
“…where R x k x k (τ ) is the space-time covariance matrix obtained following (5) in the k th frame of length L, such that n ∈ {(k − 1)L, . .…”
Section: Batch Mode Versus Frame-based Enhancementmentioning
confidence: 99%
“…The topic of polynomial eigenvalue decomposition (PEVD) has recently gained traction in the signal processing literature. Applications were found in multichannel enhancement for arbitrarily-shaped arrays [1], spherical microphones [2], or distributed microphone networks [3]; in channel identification [4]; in DOA estimation with polynomial MUSIC [5][6][7]; in voice activity detection [8]; or in beamforming with a broadband MVDR beamformer [9]. These methods rely on the estimation of a space-time covariance matrix capturing signal correlations in space, time, and frequency, thereby allowing true broadband processing [1].…”
Section: Introductionmentioning
confidence: 99%
“…The whole frequency range is considered in SP-MUSIC [14]. However, in this work, only Ω k in the frequency range of speech (100 Hz to 4000 Hz) [29] are used in (11). A peak detection algorithm [30] is used to estimate the DoAs from (11).…”
Section: Proposed Enhancements For Sound Source Localizationmentioning
confidence: 99%
“…Most of these extensions rely on transforming the broadband DoA problem into several narrowband problems. This can be achieved by decomposing the broadband signal into several independent frequency bins [11]. The resulting narrowband signals for each frequency bin or filtered output can then be processed independently, or incoherently.…”
Section: Introductionmentioning
confidence: 99%
“…The problem of designing a suitable FIR eigenvector matrix U(z) has been the stuff of many research papers, a number of which have considered applications to, for example, subband coder design (Tkacenko 2010;Redif et al 2011), MIMO channel coding (Moret et al 2011), direction of arrival estimation (Alrmah et al 2013), image compression (Carcenac et al 2017) and blind source separation (Redif 2015;Redif et al 2017). The SMD algorithm in and Corr et al (2014) was shown to provide superior convergence speeds when diagonalizing parahermitian matrices.…”
Section: U(z)ũ(z)mentioning
confidence: 99%